I fotsporene til Robert Falcon Scott - Danning, Petter (Været: populærvitenskapelig tidsskrift, 1988)
Keywords: Antarktis; ekspedisjoner; historie

Mot 90⁰ syd, en rapport - Kristensen, Monica (Polarboken, 1988)
Keywords: Antarktis; ekspedisjoner; glasiologi

Ekspedisjonen til Peter I Øy - Svendsen, Knut; Eiken, Trond (Polarboken, 1988)
Keywords: Peter I. Øy; ekspedisjoner; kartlegging; naturvitenskap

Amundsens sydpolferd 1910-12: vitenskapelige resultater sett i lys av nyere målinger - Dannevig, Petter (Været: populærvitenskapelig tidsskrift, 1987)
Keywords: Antarktis; ekspedisjoner; historie; meteorologi

Fra Monica Kristensens antarktisekspedisjon 1986-87 - Dannevig, Petter (Været: populærvitenskapelig tidsskrift11, 1987)
Keywords: Antarktis; ekspedisjoner

The South Pole expedition 1910-1912 - Huntford, Roland (The Amundsen photographs, 1987)
Keywords: Antarktis; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; ekspedisjoner; forskning; fotografihistorie; historie; oppdagelsesreiser; polarområdene

Mannen med pappnesen (Polarboken, 1986)
Keywords: Antarktis; ekspedisjoner; fotografi; historie

Monica på veg til 90° syd - Heimark, Kjell Gunnar (Været: populærvitenskapelig tidsskrift, 1986)
Keywords: Antarktis; ekspedisjoner

Fugler i de norske deler av Antarktis - Mehlum, Fridtjof (Vår fuglefauna, 1986)
Keywords: Bouvetøya; Dronning Maud Land; NARE 1984/85; Peter I. Øy; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Petreller i Dronning Maud Land - Mehlum, Fridtjof (Polarboken, 1986)
Keywords: Dronning Maud Land; NARE 1984/85; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Swedish Antarctic research. A historical Review - Liljequist, Gösta H (Sweden and Antarctica, 1985)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning; meteorologi

The Norwegian with Scott: Tryggve Gran's Antarctic diary 1910-1913 - Gran, Tryggve; Hatterlsey-Smith, Geoffrey (National Maritime Museum, 1984)
Keywords: Antarktis; dagbøker; ekspedisjoner; historie

The mineral resources of Antarctica: progress in their identification - Gjelsvik, Tore (Antarctic Resources Policy: Scientific, Legal and Political Issues, 1983)
The increment in informationCareful geological investigations started at a few places in Antarctica after World War II, but gained momentum and became systematic only when the International Geophysical Year started, and when SCAR and its Working Group on Geology were established just 25 years ago. Although geology was not initially part of the IGY programme, it soon became one of the thriving sciences in Antarctica.The growth of Antarctic geosciences can be shown in many ways, for example by the expansion of the Symposium volumes from the first one in 1963, containing 76 papers, to the latest one in August 1982, with 191 papers.The investigations have largely had the character of regional reconnaissance surveys, and the observations have mostly been published as general descriptions with maps at the scale of 1:1 million or smaller. Only one Antarctic nation has a systematic mapping programme of larger scales (1:500,000). In a few cases, such as in areas around some larger stations, more detailed work has been going on, in some cases also related to mineral occurrences. A few programmes are under way that have aspects of being resource-oriented: investigations of the Dufek Massif, a layered intrusion similar to the Cr-, Pt- and Ni-rich Bushfeld complex in South Africa, and sampling of manganese nodules during marine geological surveys. Airborne radiometric surveys and also some marine seismic surveys conducted by national oil companies or by resource-oriented state agencies belong to this category.
Keywords: Antarktis; ekspedisjoner; forskning; geologi; mineraler; ressurser

Norge og den sovjetiske polarforskning i nord og sør - Magnus, Morten H (Farmand, 1983)
Keywords: Antarktis; ekspedisjoner; polarforskning; polarområdene

Insekter i Antarktis - Sømme, Lauritz (Forskningsnytt, 1983)
Keywords: Dronning Maud Land; ekspedisjoner; entomologi; forskning; insekter; zoologi

Sommer i Antarktis: blant pingviner, sel og hvalfangstminner - Sømme, Lauritz (Universitetsforlaget, 1983)
Keywords: Antarktis; Bouvetøya; Sørishavet; ekspedisjoner; forskning; natur; økologi

Marine geophysical research in the Weddell Sea during the Norwegian Antarctic research expedition of 1976-77 - Fossum, Bjørn A.; Maisey, Georg H.; Torsen, Hans Olav (Antarctic geoscience : Symposium on Antarctic Geology and Geophysics, Madison, Wisconsin, U.S.A., August 22-27, 1977, 1982)
Keywords: NARE 1976/77; Sørishavet; Weddellhavet; ekspedisjoner; geologi; marin geofysikk

Seismic reconnaissance survey in the Weddell Sea - Haugland, Kristen (Symposium on Antarctic Geology and Geophysics, 1982)
Keywords: NARE 1976/77; Sørishavet; Weddellhavet; ekspedisjoner; havbunnen; sedimentologi; seismologi

Geology and petrology of the Southern Heritage Range, Ellsworth Mountains - Hjelle, Audun; Ohta, Yoshihide; Winsnes, Thore S. (Symposium on Antarctic Geology and Geophysics, 1982)
Keywords: Antarktis; ekspedisjoner; geologi; petrologi

Carsten Borchgrevink: lederen for den første overvintring i Antarktis - Ingstad, Helge (Polarboken, 1982)
Keywords: Antarktis; biografi; ekspedisjoner; historie

Iceberg response to sea state - Orheim, Olav; Wadhams, Peter; Kristensen, Monica (Iceberg research, 1982)
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; ekspedisjoner; forskning; isberg; isfjell; målinger

The geology, volcanic activity, and age of Bouvetøya, South Atlantic - Prestvik, Tore (Norwegian Antarctic Research Expeditions (1978/79), 1982)
Keywords: Bouvetøya; ekspedisjoner; forskning; geologi; vulkaner

Adaptation to low temperature in Antarctic terrestrial arthropods - Sømme, Lauritz (Comite National Francais Des Recherches Antarctiques, 1982)
Keywords: Antarktis; ekspedisjoner; forskning; kuldetoleranse; virvelløse dyr

Sea bed feauters in the Blåenga area, Weddell Sea, Antarctica - Lien, Reidar (Université Laval, 1981)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; geologi; havbunnen; kongress; oseanografi; symposium

Model for submarine glacial deposition - Orheim, Olav; Elverhøi, Anders (Annals of Glaciology, 1981)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; forskning; geologi; havbunnen; oseanografi

Measurements of the radiation temperature of Antarctic icebergs and the surrounding surface water - Foldvik, Arne; Gammelsrød, Tor; Gjessing, Yngvar (Annals of Glaciology, 1980)
Keywords: NARE 1978/79; Sørishavet; ekspedisjoner; glasiologi; havis; is; isbreer

Studies of icebergs, ice fronts and ice walls using side-scanning sonar - Klepsvik, John O; Fossum, Bjørn A (Annals of Glaciology, 1980)
Keywords: Dronning Maud Land; NARE 1978/79; ekspedisjoner; forskning; glasiologi; is; isberg; isfjell; isfront; morfologi; snø

De to siste fra Sydpol-ferdene 1910-12 - Omberg, Asbjørn (Polarboken, 1980)
Keywords: Antarktis; biografi; ekspedisjoner; historie

Huntfords bok om Scott og Roald Amundsen - Omberg, Asbjørn (Polarboken, 1980)
Keywords: Antarktis; ekspedisjoner; historie; litteratur

Fra et opphold på Bouvetøya i 1979 - Vinje, Torgny E (Polarboken, 1980)
Keywords: Bouvetøya; ekspedisjoner; zoologi